The Interplay of Infidelity, Sexuality, and Religiosity in the Discourse of Mixed-Orientation Marriages: A Discursive Psychological Analysis - Zulkffli, Mohd Asyraf; Ab. Rashid, Radzuwan; Kamarul Azlan, Mohammad Affiq; Ismail, Hanita Hanim (Frontiers in Psychology, 2022)
This research examines the complex interplay of religiosity, sexuality, and infidelity. We adopted a case study approach in this research, and discourse was made central to the analysis. There were two participants; both identify as homosexuals. One participant, Fahrin, is married while the other, Muzz, is divorced at the time of the interview. The participants were subjected to an in-depth, semi-structured interview to gauge their experiences, perceptions, opinions, beliefs, and thoughts on their sexuality, Islamic faith as well as relationship with their spouses. The data were then transcribed and analyzed using the Discursive Action Model (DAM) and Discursive Psychology (DP) frameworks. From the analysis, two overarching themes were identified. They are 1) The allocation of blame and accountability, and 2) the participants’ attachment to their Islamic identity. The discussion then revolves around the societal role that pressures gay men to marry women and contextualizes the position of Islam on Homosexuality.